Філософсько-психологічне підґрунтя національної самоідентифікації ліричного героя в сучасній українській поезії (на матеріалі творчості Івана Андрусяка) - Урись, Тетяна; Urys, Tetiana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Іван Андрусяк створює нову оригінальну за змістом та формою, але національно закорінену лірику. Національна самоідентифікація має свою філософсько-психологічну основу. Ліричний герой І. Андрусяка визначає себе у світі, позиціонуючись як українець, якому не байдужа доля його України, і кожна його збірка є підтвердженням цьому. The modern Ukrainian poetry tries to move away from the usual and traditional stereotypes of all kinds. Ivan Andrusyak is one of its members, creating new original content and form but nationally rooted lyrics. National self-identification of lyric author’s «I» has a philosophical and psychological basis, which is due outlook, birthplace, religion, culture of the poet, the choice of his values, the ratio of public and private property, as well as internal psychological processes of the writer’s individual, peculiar reactions to external events as irritants, psychological characteristics, temperament and character of the author. Among all the features of Andrusyak’s poetry we determine the mode of his national identity. Under a layer encoded lexicon is hidden essence of Ukrainian. The surrounding world does not exist outside of consciousness lyrical subject. The author builds his inner world on the basis of Ukrainian nature. Therefore, in his poetry Ukrainian national image of the world appears before us. The book «Pysaty myslite» contains portraits of figures of Ukrainian and world culture, poetry, reflection on art, lyrical direct appeal to Ivan Franko, allusions to the works of Taras Shevchenko and others. The purely author’s Christian worldview is reflected in his poetry, Ukrainian world is permeated extremely strong love for his country, its people, territory, nature and more. The lyrical hero of Ivan Andrusyak defines himself in the world as Ukrainian who is not indifferent to the fate of his Ukraine.
Philosophical and Psychological Basis of National Self-identification in Contemporary Ukrainian Lyrical Poetry (Based on the Works of Ivan Andrusіak)
Keywords: ліричний герой; ідентичність; національна самоідентифікація; Іван Андрусяк; lyrical hero; identity; national self-identification; Ivan Andrusіak